Качественный состав офицерских кадров российской империи во второй половине ХIХ ст.: от корпоративного к всесословному - Стоян, Т.А. (Культура народов Причерноморья, 2005)
Стаття присвячена історії пошуку шляхів вдосконалення офіцерського корпусу Російської імперії другої половини ХІХ ст. Проаналізовано процес перетворень в системі комплектування офіцерського складу військ. З'ясовано суть цього явища, мета, труднощі та результати впровадження. При написанні статті використані проблемно-хронологічний, порівняльно-історичний та статистико-аналітичний методи дослідження. Статья посвящена истории поиска путей усовершенствования офицерского корпуса Российской империи второй половины ХІХ ст. Проанализирован процес преобразований в системе комплектования офицерского состава войск. Выяснена суть этого явления, трудности и результаты внедрения. При написании статьи использованы проблемно-хронологический, сравнительно-исторический и статистико-аналитический методы исследования. The article is devoted to the history of the search of the ways of improvement of Russian officers' structure at the second half of the 19th century. The process of improvement in the system of bringing up to the strength the officers' part of Russian army has been analyzed. The essence of this phenomenon, the aim, the obstacles, the results of introduction have been turned out. Problem-chronological, comparative-historical, statistical-analytical methods of research have been used.